Preparing millennials for tomorrow: The evolution of character education in Indonesian Islamic Boarding Schools - Yusutria, Yusutria; Charles, Charles; Yuliana, Anaas Tri Ridlo Dina; Yuherman , Yuherman (Universitas Ahmad Dahlan, 2024)
The golden generation of the Indonesian nation is superior, and the millennial generation needs to be prepared to face the social order culture, world of work, scientific advances, technology, and digitization of big data. Therefore we need an educational process that links and matches with the industrial world and global changes in the future without abandoning noble character. Character education for Indonesia's golden generation is also carried out in Islamic educational institutions, namely Islamic boarding schools; Islamic boarding schools can be seen as social capital in developing Indonesian human resources. The concept of character education is also carried out and applied at the Aufia Thayyiba International Islamic Boarding School Agam West Sumatra Islamic Boarding School, with the principles of Panca Jiwa Pondok, in building the character of the golden generation of the Indonesian nation. This study aimed to determine the formation of the nature of the golden age of the Indonesian country based on the Panca Jiwa Pondok at the Aufia Thayyiba International Islamic Boarding School Agam Islamic Boarding School, West Sumatra. This research is qualitative research using a phenomenological approach. The subjects of this study were the director of the boarding school, the leadership of the boarding school, and the teachers. Data collection methods are interviews with purposive sampling techniques, observation, and documentation. The data is then analyzed using the inductive method, which emphasizes and describes the words and draws conclusions from these observations. The study results show that the formation of the character of the golden generation of the Indonesian nation is Aufia Thayyiba Agam International Islamic Boarding School by making the Panca Jiwa Pondok a philosophical foundation for its students to build character coupled with excellent programs and suitable methods.